Egyetemi jubileumokon innen és túl - Polyák, Petra (Per Aspera ad Astra, 2017)
University Jubilees and University History Writing. A Challenging Relationship. Szerk. Dhondt, Pieter. Leiden – Boston, 2015. 255 oldal (Scientific and Learned Cultures and Their Institutions 13.)